A unique method for estimating the reliability learning curve of optic nerve sheath diameter ultrasound measurement - Zeiler, Frederick A.; Ziesmann, Markus T.; Goeres, Patrick; Unger, Bertram; Park, Jason; Karakitsos, Dimitrios; Blaivas, Michael; Vergis, Ashley; Gillman, Lawrence M. (Critical ultrasound journal, 2016)
Background Optic nerve sheath diameter (ONSD) measurement using ultrasound has been proposed as a rapid, non-invasive, point of care technique to estimate intra-cranial pressure (ICP). Ultrasonic measurement of the optic nerve sheath can be quite challenging and there is limited literature surrounding learning curves for this technique. We attempted to develop a method to estimate the reliability learning curve for ONSD measurement utilizing a unique definition of reliability: a plateau in within-subject variability with unchanged between-subject variability. Methods As part of a previously published study, a single operator measured the ONSD in 120 healthy volunteers over a 6-month period. Utilizing the assumption that the four measurements made on each subject during this study should be equal, the relationship of within-subject variance was described using a quadratic-plateau model as assessed by segmental polynomial (knot) regression. Results Segmental polynomial (knot) regression revealed a plateau in within-subject variance after the 21st subject. However, there was no difference in overall mean values [3.69 vs 3.68 mm ( p = 0.884)] or between-subject variance [14.49 vs 11.92 ( p = 0.54)] above or below this cutoff. Conclusions This study suggests a significant finite learning curve associated with ONSD measurements. It also offers a unique method of calculating the learning curve associated with ONSD measurement.